All-epiphyseal anterior cruciate ligament reconstruction yields superior sports performances than the trans-epiphyseal technique in skeletally immature patients: a systematic review - Filippo Migliorini; Marco Pilone; Michael Kurt Memminger; Jörg Eschweiler; Riccardo Giorgino; Nicola Maffulli (Journal of Orthopaedics and Traumatology, 2024)
Abstract Background Anterior cruciate ligament (ACL) tears in skeletally immature patients are increasingly common. Evidence comparing the outcomes of all-epiphyseal versus trans-epiphyseal ACL reconstruction in skeletally immature patients is limited, and the current literature could benefit from a comprehensive systematic review. The present study compared all-epiphyseal versus trans-epiphyseal ACL reconstruction in skeletally immature patients. The outcomes of interest were to compare joint laxity, patient-reported outcome measures (PROMs), return to sport, and complications. Methods This study was conducted according to the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. In November 2023, the following databases were accessed: PubMed, Web of Science, Google Scholar, and Embase. No additional filters were used in the database search. All the clinical studies investigating ACL reconstruction in skeletally immature patients were accessed. Only articles that clearly stated the surgical technique (all- or trans-epiphyseal) were eligible. Only articles with a minimum of 6 months of follow-up were included. Only articles that clearly stated that surgeries were conducted in children with open physis were eligible. Results Data from 1489 patients (1493 procedures) were collected, of which 32% (490 of 1489 patients) were female. The mean length of follow-up was 46.6 months. The mean age of the patients was 12.7 years. No difference was found in joint laxity (Table 3): positive pivot shift (P = 0.4), positive Lachman test (P = 0.3), and mean arthrometer laxity (P = 0.1). No difference was found in PROMs (Table 4): International Knee Documentation Committee (IKDC) (P = 0.3), Lysholm (P = 0.4), and Tegner (P = 0.7). The trans-epiphyseal technique was associated with a greater rate of patients unable to return to sports (1% versus 7%, P = 0.0001) and with a longer time to return to sports (7.7 versus 8.6 months, P = 0.01). Though the trans-epiphyseal technique was associated with a lower rate of return to sport, this difference was not statistically significant (P = 0.8). No difference was evidenced in the rate of patients who had reduced their league or level of sports activity (P = 0.6) or in the rate of patients who had returned to their previous league or level of sports activity (P = 0.7). No difference was found in the rate of complication: re-tear (P = 0.8), reoperation (P = 0.7), increased laxity (P = 0.9), and persistent instability sensation (P = 0.3). Conclusion Trans-epiphyseal ACL reconstruction was associated with a greater rate of patients unable to return to sport and with a longer time to return to sport compared with the all-epiphyseal technique in skeletally immature patients. Level of evidence Level III, systematic review.